Study on Microstructure Distribution of Al-Cu-Mg Alloy in Squeeze Casting Process. Issue 1 (1st September 2022) - Li, Longfei; Zheng, Yuankai; Chen, Yunbo; Feng, Jian; Li, Chunming; Chen, Lin; Zuo, Lingli; Zhang, Yang
Abstract: The squeeze casting process is an advanced technology, which is suitable for a wide range of alloys including Al-Cu-Mg alloys. The high pressure in squeeze casting process both refines the microstructure and enhances the mechanical property of the alloys. The heat transfer and solidification process are complex with the chilling mould and pressure of machine punch. This results in the inhomogeneous microstructure and property in casting alloy. This study focuses on the distribution of microstructure, chemical composition, and hardness of Al-Cu-Mg alloy along the radial direction of casting. The composition and area fraction of eutectic phases are characterized. Moreover, the relationship between the microstructure and mechanical property was also analysed to show the characteristic of microstructure in squeeze casting process.